Phonological Representations Are Unconsciously Used when Processing Complex, Non-Speech Signals - Azadpour, Mahan; Balaban, Evan (PloS one, 2008)
Neuroimaging studies of speech processing increasingly rely on artificial speech-like sounds whose perceptual status as speech or non-speech is assigned by simple subjective judgments; brain activation patterns are interpreted according to these status assignments. The naïve perceptual status of one such stimulus, spectrally-rotated speech (not consciously perceived as speech by naïve subjects), was evaluated in discrimination and forced identification experiments. Discrimination of variation in spectrally-rotated syllables in one group of naïve subjects was strongly related to the pattern of similarities in phonological identification of the same stimuli provided by a second, independent group of naïve subjects, suggesting either that (1) naïve rotated syllable perception involves phonetic-like processing, or (2) that perception is solely based on physical acoustic similarity, and similar sounds are provided with similar phonetic identities. Analysis of acoustic (Euclidean distances of center frequency values of formants) and phonetic similarities in the perception of the vowel portions of the rotated syllables revealed that discrimination was significantly and independently influenced by both acoustic and phonological information. We conclude that simple subjective assessments of artificial speech-like sounds can be misleading, as perception of such sounds may initially and unconsciously utilize speech-like, phonological processing.